2022
DOI: 10.3390/pharmaceutics14051109
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired and Biomimetic Nanomedicines for Targeted Cancer Therapy

Abstract: Undesirable side effects and multidrug resistance are the major obstacles in conventional chemotherapy towards cancers. Nanomedicines provide alternative strategies for tumor-targeted therapy due to their inherent properties, such as nanoscale size and tunable surface features. However, the applications of nanomedicines are hampered in vivo due to intrinsic disadvantages, such as poor abilities to cross biological barriers and unexpected off-target effects. Fortunately, biomimetic nanomedicines are emerging as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 202 publications
0
6
0
Order By: Relevance
“…Compared with traditional diagnosis and treatment methods of cancer, NMs provide an alternative strategy for t tumor argeted therapy due to their unique physical and chemical properties, such as nanoscale size, large surface-to-volume ratio, adjustable surface characteristics, and the ability to encapsulate various drugs and control drug release [260]. For a long time, in the study of tumor targeted therapy, improving the efficiency of tumor targeting is the key issue and main technical difficulty in the development of high-quality tumor-targeted NMs [261]. Although existing studies have reported the wide application of various NMs in cancer therapy, there are still some limitations that need to be overcome, such as the interaction mechanism between NMs and cells, short blood circulation time, and poor aggregation in target tissues.…”
Section: Cancermentioning
confidence: 99%
“…Compared with traditional diagnosis and treatment methods of cancer, NMs provide an alternative strategy for t tumor argeted therapy due to their unique physical and chemical properties, such as nanoscale size, large surface-to-volume ratio, adjustable surface characteristics, and the ability to encapsulate various drugs and control drug release [260]. For a long time, in the study of tumor targeted therapy, improving the efficiency of tumor targeting is the key issue and main technical difficulty in the development of high-quality tumor-targeted NMs [261]. Although existing studies have reported the wide application of various NMs in cancer therapy, there are still some limitations that need to be overcome, such as the interaction mechanism between NMs and cells, short blood circulation time, and poor aggregation in target tissues.…”
Section: Cancermentioning
confidence: 99%
“…Viral nucleocapsid structures can activate the innate immune system through various signaling pathways. For example, the cell surface receptors involved in the recognition of viral proteins (e.g.,TLR2 and TLR4) and nucleic acids (e.g., TLR3, TLR7, TLR8, and TLR9), which confer viral immunity through TLRs . In addition, the virus at 20–500 nm can enter lymph nodes and be captured by innate immune cells to kickstart the immune system, making it ideal for immunotherapy.…”
Section: Application Of Bnds In Tumor Immunotherapymentioning
confidence: 99%
“…For example, the cell surface receptors involved in the recognition of viral proteins (e.g.,TLR2 and TLR4) and nucleic acids (e.g., TLR3, TLR7, TLR8, and TLR9), which confer viral immunity through TLRs. 140 In addition, the virus at 20−500 nm can enter lymph nodes and be captured by innate immune cells to kickstart the immune system, making it ideal for immunotherapy. However, their application still has room for controversy, such as low biosafety and off-target effects.…”
Section: Platelets and Platelet Membranes (Pms)mentioning
confidence: 99%
See 2 more Smart Citations